Application of the fractal analysis in the sea bottom recognition - ŁUBNIEWSKI, Z.; STEPNOWSKI, A. (Archives of Acoustics, 1998)
The paper proposes a newly developed simple method of the sea bottom typing using elements of fractal analysis. The fractal dimension was calculated as a box dimension for sampled envelopes of echo signals from four types of sea bottom recorded during mobile acoustic surveys carried out in Lake Washington. The histograms of obtained box dimension values for particular bottom types as well as scatter diagrams in box dimension-echo energy parameter space were constructed and analysed. The obtained results show that this simple method can be used both alone and combined with other methods for on board sea bed recognition in real time with accuracy similar to that of other methods.